Meshless simulation of anti-plane crack problems by the method of fundamental solutions using the crack Green's function. (1st March 2020) - Ma, Ji; Chen, Wen; Zhang, Chuanzeng; Lin, Ji
Abstract: In this paper, we present a meshless method of fundamental solutions using the analytical crack Green's function to solve anti-plane crack problems. The proposed scheme is a simple, powerful and effective collocation method for crack problems since it only requires the boundary discretization without special treatments of the crack. Three typical numerical examples, namely, a central crack, an off-central crack and a central slant crack are presented and discussed to illustrate the accuracy, convergence and stability of the proposed method.